Production and acceptability testing of fish crackers (‘keropok’) prepared by the extrusion method - Yu, S. Y.; Mitchell, J. R.; Abdullah, A. (Institute of Food Science and Technology, 1981)
‘Keropok’, a traditional Malaysian snack food composed of fish and flour, was successfully prepared by extrusion. The degree of expansion of the dried product on frying was measured as a function of extruder temperature and the ratio of fish to tapioca flour in the product. It was found that expansion decreased with increasing fish content. Organoleptic evaluation indicated that the extruded products were as acceptable as those prepared using traditional methods.